Analisis Kebijakan Perencanaan Keuangan di Fakultas Adab dan Humaniora, UIN Alauddin Makassar - Siti Jauhari; Mukhtar Alshodiq (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2024)
This Policy Paper describes financial planning policy issues at the Faculty of Adab and Humanities (FAH) UIN Alauddin Makassar, which focuses on (1) the process of preparing financial planning policies, (2) elements and provisions contained in financial planning policies, (3) implementation financial planning policies at FAH UIN Alauddin Makassar, as well as (4) monitoring and evaluating the effectiveness and efficiency of financial planning policies. This study uses a qualitative method with a case study approach, where data is collected through interviews with key informants, observation, and documentation. The results show that the financial planning policy at FAH UIN Alauddin Makassar has been well formulated and involves various parties. However, there are several obstacles in implementing policies, such as a lack of understanding by staff and limited resources as well as monitoring and evaluation of the effectiveness and efficiency of financial planning policies. Thus, financial planning policies at FAH UIN Alauddin Makassar need to be optimized by: (1) Increasing staff understanding of policies through education and training; (2) Strengthening monitoring and evaluation systems to ensure policy effectiveness and efficiency; and (3) Improving coordination between various parties involved in financial planning.